Valorization of Sargassum tenerrimum: Value addition using hydrothermal liquefaction. (15th June 2018) - Biswas, Bijoy; Fernandes, Alisha C.; Kumar, Jitendra; Muraleedharan, Usha D.; Bhaskar, Thallada
Highlights: Hydrothermal liquefaction was carried out for bio-oil production from S. tenerrimum . Maximum bio-oil yield was obtained (16.33 wt%) at 280 °C. High percentage of aliphatic functional groups was observed in all bio-oils. Bio-residue obtained at various temperatures was showed typical amorphous nature. Abstract: Sargassum tenerrimum has been used for the production of bio-oil by hydrothermal liquefaction in water sub-critical conditions at a temperature range of 260–300 °C for reaction time 15 min. Maximum bio-oil (16.3 wt%) was obtained at 280 °C and maximum conversion was observed (75.8 wt%) at 300 °C. The solid residue yields decreased continuously from 61.2 wt% to 24.2 wt% as the temperature increased from 260 to 300 °C. The liquid products obtained upon hydrothermal liquefaction were characterized with the help of 1 H NMR, GC–MS and FT-IR techniques and bio-residue using FT-IR and XRD. Analysis of bio-oil showed that their components and functional structure of bio-oils were greatly distinguished and consisted of many compounds including phenols, ketones, aldehydes, acid, esters, alcohols, nitrogen-containing compounds, and hydrocarbons. From the GC–MS analysis it has been seen that, organic acid content in the bio-oils were decreased with the increasing temperature from 260 to 300 °C. The band at 1083 cm −1 only appeared in the absorption profile of S. tenerrimum feed, which could be C-O connected with hydroxyl groups and were dehydrated after liquefaction. All the bio-oils showed higher percentages of aliphatic protons in the spectral region from 0.5 to 3.0 ppm. The analysis of bio-residue obtained at various temperatures showed typical amorphous nature that indicated richness of carbon content in the residue.